Improved strain sensing properties of cement-based sensors through enhanced carbon nanotube dispersion. (January 2021) - D'Alessandro, Antonella; Tiecco, Matteo; Meoni, Andrea; Ubertini, Filippo
Abstract: New multifunctional materials are under continuous development in various fields of the scientific and technological panorama, due to the enhanced applications they concern. Among these materials, cement-based composites appear particularly noticeable for their real impact on engineering and, in particular, for their use as structural materials. A pioneering application of such multifunctional materials is the monitoring of the stresses and strains of structures during their service conditions by use of embedded cementitious sensors doped with smart conductive fillers, such as carbon nanotubes. The homogeneity of the sensors is essential for their reliability and the dispersion techniques result a delicate task. The paper proposes a novel surfactant dispersion additive for improving conductivity and strain-sensing properties of cement-based sensors (DDA) and compares its behavior with that of conventional ones. Chemical, electrical and electromechanical tests have been carried out to demonstrate the superiority of the proposed surfactant and the resulting improvement in functional properties of the novel cementitious composite material for applications in constructions. The samples with the novel dispersant DDA, developed by the Authors, exhibit higher gauge factors, higher linearity, with reduced drift and hysteresis behavior.